Research on Lung Medical Image based on Convolution Neural Network Algorithm. Issue 3 (March 2021) - Xu, Yipeng; Zhu, Yiming; Chen, Zhongrun
Abstract: In the field of medical image processing, the convolution neural network (CNN) algorithm in depth learning solves many problems in machine vision.Aiming at the problems of low resolution of medical images and easy misjudgment of artificial recognition, in order to help medical workers to better identify the lesion area, this paper discusses the structure optimization, training and prediction ability of CNN, and trains the convolution neural network to judge the lesion area in the image.and get more accurate discriminant results on lung images, further verify the high efficiency, accuracy and reliability of convolutional neural network algorithm in medical image field.